Development of a fast method for optimization of Au ball bond process. Issue 3 (February 2015) - Gomes, J.; Mayer, M.; Lin, B.
Highlights: A fast method to optimize ball bond parameters for Au wire is developed. Parameters are optimized separately for bond geometry and bond strengthening. Presented method utilizes existing process knowledge, DOEs, and iteration. Method is verified by optimizing ball bond parameters for Pd coated Cu (PCC) wire. Abstract: An accelerated optimization method is developed to minimize required time and resources, and demonstrated for a 25 μm diameter Au ball bonding process. After a preparation phase to pre-set many parameters based on literature values, the values for more significant process parameters, impact force (IF) and EFO time ( t EFO ) for a given target bond geometry are optimized in a second phase, utilizing a 3 2 full factorial experiment and the response surface method (RSM). The target bond strength of 120 ± 2 MPa is achieved in a third phase by optimizing the ultrasonic energy (US) parameter using an iterative method. For an example process with a target geometry of 58 μm for the bonded ball diameter measured at the capillary imprint (BDC) and 16 μm for the height of the bonded ball (BH), the optimized process parameters (phases 2 & 3) can be found in less than 4 h. The values for IF and t EFO are found to be 424 mN and 0.474 ms, respectively. The bond is strengthened with incrementing US until additional ball deformation occurs. The bond strength achieved is >120 MPa with 48.6% US. Other bonding parameters include EFO current ( I EFO ) = 50 mA, temperature (T) = 158 °C, bond time (Bt) = 20 ms, and bond force (BF) = 185 mN.